2015
DOI: 10.1017/s0373463315000521
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Collision Potentials in Port Anchorages: Application of the Navigational Traffic Conflict Technique (NTCT)

Abstract: Despite the extent of works done on modelling port water collisions, not much research effort has been devoted to modelling collisions at port anchorages. This paper aims to fill this important gap in the literature by applying the Navigation Traffic Conflict Technique (NTCT) to measuring the collision potentials in anchorages and for examining the factors contributing to collisions. Building on the principles of the NTCT, a collision potential measurement model and a collision potential prediction model were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 27 publications
0
7
0
2
Order By: Relevance
“…Даны лишь рекомендации относительно того, каким образом пассажирским судам следует избегать отмеченные участки. Схожий подход используется также в работе [34].…”
Section: обсуждение (Discussion)unclassified
“…Даны лишь рекомендации относительно того, каким образом пассажирским судам следует избегать отмеченные участки. Схожий подход используется также в работе [34].…”
Section: обсуждение (Discussion)unclassified
“…Vessel collisions occur most frequently in busy ports or fairways. 4,[9][10][11][12][13][14] Yip 4 reported that there have been many previous studies that discussed marine accidents. However, most of them focused on the relationship between marine accidents and ship characteristics, flag nationality, and crew.…”
Section: Ship Collisionmentioning
confidence: 99%
“…Vessel collisions occur most frequently in busy ports or fairways. 4,[9][10][11][12][13][14] Li et al 13 reviewed some quantitative risk assessment models for evaluating ship collision risk. In their review, they suggested that it is necessary for future studies to take two issues into account: human factor and parameter uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…The negative correlation between DTD and Meandis is significant, thereby proving that DTD can represent the density and compactness of ships effectively. Moreover, it is known that port areas always have relatively high ship density due to their large trade volume and the limited navigation conditions (Debnath and Chin, 2016). As a result, the density and compactness of ships in the port area should be greater than for other, wide open water areas, which can be proved by the results in Table 1, representing that the results of the experiment are consistent with the real-world situation.…”
Section: Case Studymentioning
confidence: 99%